PERSEPSI MASYARAKAT TENTANG INFRASTRUKTUR DAN SOSIAL EKONOMI DI JORONG BANDUA BALAI DAERAH PERBATASAN KABUPATEN PASAMAN BARAT DENGAN PASAMAN - -, Bakar - (Pendidikan Geografi, 2014)
This research is purposed to get information about Societyâs perception on infrastructure and social economic at Jorong Bandua Balai as an area border of West Pasaman with Pasaman.district about it is one of the road to connect Kinali With Pasaman. This research is a qualitative. The research Informants of this research is society of Jorong Bandua Balai. The technique for informant is snowball sampling. The result of this research such as. 1) during ten years, condition of infrastructure at Jorong Bandua Balai damaged because less attention from goverment to repair infrastructure physically. So society have difflculty to access the area of Jorong Bandua Balai and it have an impact to economic like trade. Society desire that the goverment can repair infrastructure at Jorong Bandua Balai as an border area. 2) based on perception of society about social economic of border area of Jorong Bandua Balai, that relationship of individuals is run well and they have good behaviours because they donât get influence from outside. Generally the society of this area have livehood from farming of palm oil, patchouli oil, corn and rice. for to take so society want that the government can pay attention to the condition of infrastructure especially to the road, poskesdes and education so that can fulfill the requirements of the society as properly.